2010
DOI: 10.1016/j.tourman.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Adventure and ecotourism safety in Queensland: Operator experiences and practice

Abstract: Bentley, T. A., Cater, C. I., & Page, S. J. (2010). Adventure and ecotourism safety in Queensland: Operator experiences and practice. Tourism Management, 31(5), 563-571 Sponsorship: BBSRC; Genencor Inc.This study identifies the client injury experience and safety management practices of Queensland adventure and ecotourism operators, and to compare these findings with those from recent New Zealand surveys. The effectiveness of an on-line survey for collecting safety information from operators is evaluated in re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 29 publications
1
28
0
4
Order By: Relevance
“…Suggestion in this regard, therefore, is to strongly consider that one route to positivity in adventure participation is via developing an internal insight for adventure. Risk management should not only be done in isolation but also with the notion of balance with people's awareness of how well the risk is managed and how management of itself values consumer's personal value for the activity, making sure that safety strategies are fully and practically applied (Bentley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Suggestion in this regard, therefore, is to strongly consider that one route to positivity in adventure participation is via developing an internal insight for adventure. Risk management should not only be done in isolation but also with the notion of balance with people's awareness of how well the risk is managed and how management of itself values consumer's personal value for the activity, making sure that safety strategies are fully and practically applied (Bentley et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among the constraint variables, only risk was singled out and observed at this point, because risk has been noted as a factor that can negatively and positively affect the potential growth of mountain adventure (Callander & Page, 2003). Risk acts as a central attraction for adventure tourism, yet it is also more beneficial if it is reduced (Bentley, Cater, & Page, 2010). Using linear regression analysis and ENTER method, the result showed that the fear of risk and participation frequency have a positive correlation (R = 0.06), but the correlation was insignificant (p = 0.15).…”
Section: Risk As a Constraint Personal Value And Participationmentioning
confidence: 99%
“…The notion that adventure tourism is only for the young is becoming harder to defend as participation rates across the generations are growing (Mintel, 2010). The gender gap with regards to participation numbers is also rapidly dissolving (ATTA & GWU, 2013;Bentley et al, 2010). Women account for approximately 43% of adventure travelers (ATTA & GWU, 2013) and make up approximately 60% of adventure tour operator's customers, with many women traveling alone (Mintel, 2010).…”
Section: Characteristics and Lived Experiences Of Adventure Tourism Pmentioning
confidence: 99%
“…The accepted necessity for risk and uncertainty in adventure tourism activities also presents a paradox within adventure tourism operators. While clients are assumed to pay for activities involving risk and uncertainty, tour operators must minimize the risk and emphasize safety (Beedie, 2003;Bentley, Cater, & Page, 2010;Buckey, 2012). Notably, operators implement a number of control factors (e.g., technological, behavioral, and locational) that interact to minimize risk and ensure the safety of participants engaging in adventure tourism (Bentley et al, 2010).…”
mentioning
confidence: 99%
“…Produk ini dapat diintegrasikan dalam kegiatan arung jeram, antara lain: pengamatan ular, kelelawar, dan air terjun sepanjang Sungai Pekalen. Dalam pelaksanaannya kategori wisata ini membutuhkan kualitas produk yang tinggi dengan tingkat kenyamanan dan keamanan yang baik (Bentley, Cater, & Page, 2010;Bentley, Page, & Walker, 2004).…”
Section: Tipe Produk Ekowisata Sungai Pekalen Atasunclassified